“I Wasn’t in My Right Mind”: Qualitative Findings on the Impact of Alcohol on Condom Use in Patients Living with HIV/AIDS in Brazil, Thailand, and Zambia (HPTN 063) - Brooke G. Rogers (2018)
© 2018, International Society of Behavioral Medicine. Purpose: There have been significant biomedical improvements in the treatment and prevention of HIV over the past few decades. However, new transmissions continue to occur. Alcohol use is a known barrier to medication adherence and consistent condom use and therefore may affect treatment as prevention (TasP) efforts. The purpose of this study was to further explore how alcohol is associated with condom use and sexual transmission behavior in three international cities. Method: HIV Prevention Trials Network 063 was an observational mixed-methods study of HIV-infected patients currently in care in Rio de Janeiro, Brazil; Chiang Mai, Thailand; and Lusaka, Zambia. Across these three global cities, 80 qualitative interviews were conducted from 2010 to 2012. From these interviews, quotes related to substance use, almost all of which were alcohol, were analyzed using thematic analysis to identify how the use was related to sexual transmission behaviors. Results: Overall, the theme that alcohol impairs cognitive abilities emerged from the data and included the following subthemes: expectancies, impaired decision-making, loss of control, and less concern for others. Themes specific to international settings and risk subgroups were also identified. Conclusion: Our analysis identified how alcohol influences sexual transmission behavior in HIV patients in three international settings. These findings may provide direction for content development for future secondary prevention interventions to effectively implement TasP internationally.